Sistem Pengukuran Keterampilan Pengguna Pada Simulator Las Berbasis Augmented Reality - Chairu Ummam, Mochammad; Noor Prawita, Fathah (eProceedings of Applied Science, 2023)
Abstract— In the industrial world, it certainly cannot be separated from what is called a welding process. The welding process is not cheap because the materials used are very expensive. In addition, welding skills needed to be mastered in a lot of time and materials for so that welders weld objects perfectly. In our final project titled